Hubungan Karakteristik Ibu Hamil dengan Tingkat Pengetahuan Ibu Tentang Kehamilan Berisiko di RSUDBanyumas - Uma Nurani; Alfi Noviyana (Universitas Harapan Bangsa Purwokerto, 2023)
Background: The maternal mortality rate in Indonesia is still high so preventive efforts are needed to reduce maternal mortality. The knowledge of pregnant women about risky pregnancies is a prevention of risk factors that may occur in pregnancy . Purpose: to find out the relationship between the characteristics of pregnant women (age, parity, level of education and employment status) with the level of knowledge about risky pregnancies at Banyumas Regional Hospital. Method: this research is an analytical descriptive study , with a cross sectional approach. Sampling technique with accidental sampling, the total sample was 97 respondents. The results of the study: showed that most of the respondents aged 20-35 years (74.2%), most of them had low education (elementary, junior high school) ) which was 39 people (40.2%), most of whom had 1-2 children, namely as many as 55 people (56.7%) and most of the respondents were not working, namely as many as 78 people (80.4%) . Most of the respondents had a poor level of knowledge, namely as many as 39 people (40.2%). The results of the Chi Square test obtained the results of there is a relationship between age and knowledge level (p value = 0.034) , there is a relationship between parity and knowledge level (p value = 0.001) , there is a relationship between education level and knowledge level (p value = 0.000) and there is a relationship between job status and knowledge level (p value = 0.005). Conclusion: There is a meaningful relationship between the characteristics of pregnant women (age, parity, education level and employment status) and the level of knowledge about risky pregnancies at Banyumas Regional Hospital.